2014
DOI: 10.2478/s11535-014-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of sunflower (Helianthus annuus L) genotypes to PEG-mediated water stress

Abstract: Drought tolerance of two sunflower (Helianthus annuus L.) genotypes, cultivated cultivar 1114 and interspecific line H. annuus × H. mollis, was studied under laboratory conditions using PEG-6000. Four levels of osmotic stress (-0.4, -0.6, -0.8 and -1.0 MPa) were created and performances were monitored against a control. Physiological and biochemical stress determining parameters such as malondialdechyde (MDA), proline content, and hydrogen peroxide (H 2 O 2 ) were compared between seedlings of both genotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…De Leonardis, Petrarulo, De Vita, and Mastrangelo (2012) consider that the improvement of drought tolerance represented, and still represents, one of the major objectives of plant breeding. Sunflower genotypes may perform differently under different drought levels, and genotypic differences in drought tolerance could be, at least in part, attributed to the ability of plants to acclimate and induce different defence mechanisms under severe water stress (Vassilevska‐Ivanova et al, 2014). According to Ahmad et al (2009), dry biomass, plant height and root length indicate that seedling growth is a reliable and efficient procedure for screening sunflower hybrids for moisture stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Leonardis, Petrarulo, De Vita, and Mastrangelo (2012) consider that the improvement of drought tolerance represented, and still represents, one of the major objectives of plant breeding. Sunflower genotypes may perform differently under different drought levels, and genotypic differences in drought tolerance could be, at least in part, attributed to the ability of plants to acclimate and induce different defence mechanisms under severe water stress (Vassilevska‐Ivanova et al, 2014). According to Ahmad et al (2009), dry biomass, plant height and root length indicate that seedling growth is a reliable and efficient procedure for screening sunflower hybrids for moisture stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed the seedling mass gradually decreasing with an increment in PEG concentration, so that in the 10% PEG variant there was only half of the seedling mass obtained compared to control (water) treatment (Table 2; 0.30 vs. 0.60 g). Vassilevska‐Ivanova et al (2014) concluded that a number of physiological and biochemical features of sunflower plants, such as seed germination, shoot and root length, fresh and dry matter content, water content and the accumulation of proline, MDA and H 2 O 2 , are directly affected by PEG‐mediated water stress. In their research, the increase of MDA content was evident under severe water stress (−1.0 MPa), and the levels of proline increased in parallel with the severity of water stress in both tested sunflower genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, many examples of oxidative stress and antioxidant defense mechanism in H. annuus subjected to drought (Kaya et al, 2006;Rauf et al, 2008;Ahmad et al, 2009;Petcu and Pâcureanu, 2011) have been reported. However, there have been limited studies concerning the response of sunflower genotypes developed after wide (interspecific or intergeneric) hybridization (Vassilevska-Ivanova et al, 2014b). In this paper we have presented two genetically stable lines that have intermediate characteristics between both parents and will likely be useful in sunflower breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Sunflower wild types have very useful genes for drought tolerant genes because some subspecies of Helianthus genus have very wide adaptation capability for drought stress conditions such as H. mollis, H. deserticola, H. hirsutus, H. maximiliani, H. tuberosus, H. argophyllus etc. [20], [21]. Therefore, cultural types have some tolerant genes especially derived from these sources and also from some land races.…”
Section: Introductionmentioning
confidence: 99%